Influence of impact velocity on energy absorption performance of thick-walled truncated conical shells - Özyurt, Erdem; Yilmaz, Haluk; Tomek, Petr (University of Pardubice, 2018)
The paper deals with the energy absorption capabilities of truncated conical structures with low base angle under quasi-static and dynamic axial loading. The simulation results were compared by means of several performance parameters such as mean crushing force Fm, absorbed energy EA, specific energy absorption (SEA), crash force efficiency (CFE), dynamic amplification factor (DAF) and absorbed energy per unit deformation. Results are summarized by means of the performance parameters and main conclusions are made.
Keywords: finite element method; energy absorption; truncated cone; crashworthiness